The Apotheosis of the Apothecary: Retailing and Consuming the Meaning of a Historic Site - Litt, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1999)
AbstractThis paper examines how history is interpreted and understood at the Niagara Apothecary, an early 1970s heritage restoration project that is operated as a Victorian-era pharmacy museum in Niagara-on-the-Lake, Ontario. It recounts the history of the restoration of this historic site to show the variety of influences and interests that have shaped the history it presents. The apothecary's setting in Niagara-on-the-Lake, a mecca for heritage tourism and consumerism, makes it an interesting case study of how history is communicated to a popular audience. To this end, the nature of the tourist experience at Niagara-on-the-Lake in general and the apothecary in particular are explored. The paper contrasts the professional historian's emphasis on objectivity and context with the material, romantic, specialised and consumer-friendly strategies that are employed in the presentation of the past at the apothecary.